اختبار كفاءة المشط الهوائي والهزاز الكهربائي على جني أشجار الزيتون صنفي الزيتي والصوراني ومقارنتها بالقطاف اليدوي - الإبراهيم, أنور; عابدين, مالك; جبارة, غسان; الجعفر, عبد المهيمن; برغل, أكرم (Latakia University Journal -Biological Sciences Series, 2019)
بدأت دراسات القطاف الآلي في سورية منذ عام 1981 باستخدام هزازات الجذع، حيث بينت النتائج تفوق إنتاجيتها مقارنة بالقطاف اليدوي إلا أنه نتيجة لكون الأشجار المختبرة غير ملائمة لهذا النوع من القطاف فقد ظهرت بعض العوائق الزراعية والتقانية على الأشجار المدروسة فضلاً عن الارتفاع في تكاليف الاستثمار. في منتصف تشرين الثاني سنة 2005 تم اختبار كفاءة نوعين من آلات القطاف المحمولة على الكتف "المشط الهوائي والهزاز الكهربائي" ومقارنتهما بالقطاف اليدوي لأشجار الزيتون في طور الإثمار ذات الشكل الكروي للصنفين الصوراني في محافظة ادلب و الزيتي في محافظة حلب، فقد أظهرت نتائج الكفاءة تفوق القطاف اليدوي مقارنة بالآلي بشكل بسيط (2-4)% إذ بلغت كفاءة القطاف الآلي قيماً جيدة إلا أنها أقل نسبياً من قيم القطاف اليدوي التي بلغت في الصنفين الصوراني والزيتي (97-96)% من الإنتاج الكلي على التوالي كما بلغت باستخدام المشط الهوائي (95-92)% على التوالي و الهزاز الكهربائي (92)% لكلا الصنفين، في حين تضاعفت إنتاجية العامل باستخدام القطاف الآلي مقارنة باليدوي بمعدل (3.5-4) مرات في صنف الزيتي و (4.5-5) في صنف الصوراني حيث أعطى المشط الهوائي ( 47.2 - 79.3) كغ/ساعة قيماً أعلى من الهزاز الكهربائي(40.9 - 71.1) كغ/ساعة في الصنفين الصوراني والزيتي على التوالي. وفي النتيجة فإن استخدام كلا النوعين من أجهزة القطاف الآلي قد عزز إنتاجية العامل الواحد قياساً بالقطاف اليدوي( 8.8 - 19.6) كغ/ساعة ومقارنة بالقطاف اليدوي التي تشكل 100% من كلفة القطاف فإن المشط الهوائي شكل حوالي 15% منها، بينما شكل الهزاز الكهربائي 11% منها و لهذا فإن كفاءة الهزاز الكهربائي تعتبر أفضل من الناحية الاقتصادية. Studies of mechanical harvesting in Syria have begun Since 1981 by using Trunk Shakers, and they have shown a higher yield than hand harvesting, but due to the unsuitability of conventional Olive trees, they also have shown economic and agricultural technique problems , in addition to high cost. In mid November 2005, two hand-held machines, a pneumatic comb and an electric vibrator, were compared with one another and with manual harvesting, on adult trees, trained to the globe system, of the two main Syrian olive cultivars: Sorani (Idleb area) and Zeiti (Aleppo area). The results showed that manual harvesting is slightly more efficient (2-4)% compared to mechanical harvesting. The total efficiency of mechanical harvesting reached good value, but it was relatively lower than the values of the manual harvest, which totaled in both cultivars Surani and Zaiti (96-97%) of the total production, respectively, and amounted to (92-95%) respectively using a pneumatic comb, and to (92 %) using electric vibrator for both cultivars. With respect to working productivity (kg of olives detached by one worker in one hour), it also increased (3.5-4) times with the cultivar Zaiti and (4.5-5) times with the cultivar Sorani. The pneumatic comb gave higher values of (47.2 - 79.3) kg / hour compared to the electric vibrator (40.9 - 71.1) kg / h in two cultivars Surani and Zaiti, respectively. As a result, the use of both types of mechanical harvesting equipment has enhanced the productivity per worker compared to manual harvesting (8.8 to 19.6) kg / hour, and when compared to the manual harvesting which amounts to 100% of the cost of harvesting, the pneumatic comb accounted for only about 15% , while the electric whipper only 11% , and this is why the efficiency of the electric whipper is economically better.